Understanding of the effect of microbiome on human health: a chemical process engineering perspective - Chen, Xiao Dong (Frontiers in Microbiomes, 2025)
Aspects about the straightforward linking of gut health or the gut microbiota with existing diseases are critically explored. While there is a popular notion that gut health directly influences overall health and can cause or alleviate diseases, the mechanisms behind these effects are not fully understood. Chemical process engineering (CPE) concepts bring new insights into the effects of human microbiome, which may clarify the fundamental influences. The discussions presented here suggest the future directions of research, which need to be pursued for the benefit of human health.